Cytokine profile in Montenegro skin test of patients with localized cutaneous and mucocutaneous leishmaniasis - Nogueira, Marcia Ferraz; Goto, Hiro; Sotto, Mírian Nacagami; Cucé, Luiz Carlos (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
American tegumentary leishmaniasis presents as two major clinical forms: localized cutaneous leishmaniasis (LCL) and mucocutaneous leishmaniasis (MCL). The immune response in leishmaniasis is efficiently evaluated by the response to Leishmania antigen through the Montenegro skin test (MST). Both LCL and MCL present positive response to MST, indicating that the patients present cell-mediated immunity against the parasite - Leishmania. In spite of the presence of immunity in MCL, this is not sufficient to stop disease progression and prevent resistance to treatment. In this study we demonstrated interleukin (IL) 2, 4, 5 and interferon (IFN) gamma expression in biopsies of MST of ten patients with American tegumentary leishmaniasis. The obtained results were compared between LCL (n = 5) and MCL (n = 5) patients. The MST of MCL patients displayed a higher expression of IL-2, IL-4 and IL-5, in comparison to LCL. There was no significant difference in IFN-gamma expression between groups. The obtained results suggest the role of IL-4 and IL-5 in the maintenance of the immunopathogenic mechanism of the destructive lesions that characterize MCL.